Analisis Karakteristik dan Distribusi Sedimen Dasar (Bed Load) di Sungai Lesti Menuju Waduk Sengguruh - Wws, Anggara; Dian Sisinggih; Emma Yuliani; Prasetyo Rubiantoro (Jurnal Teknik Sipil Terapan (JTST), 2026)
Sedimentation is a major problem in reservoir management because it reduces storage capacity and affects operational performance. One of the main sediment sources comes from Sungai Lesti, which flows into Waduk Sengguruh. This study aims to analyze the characteristics of bed load sediment based on grain size distribution and its implications for sedimentation processes in the reservoir. The research methods included field surveys, sediment sampling using a Helley-Smith Bedload Sampler, and laboratory using sieve analysis methods. The analyzed parameters were D10, D30, D60, uniformity coefficient (Cu), and gradation coefficient (Cc). The results indicate that the sediment is dominated by fine to very fine sand with poorly graded characteristics. The values of Cu and Cc show an increase in grain size variability and a more uneven distribution at locations closer to the reservoir. Differences in sediment characteristics between upstream and downstream areas reflect the occurrence of hydrodynamic sorting due to a decrease in flow velocity. Coarser particles tend to be deposited in the river–reservoir transition zone, while finer particles are transported farther and accumulate within the reservoir body. These conditions indicate more intensive sedimentation processes near the reservoir, which may accelerate siltation and reduce storage capacity in the long term. Therefore, integrated and sustainable sediment management is required to maintain the long-term functionality of the reservoir. Keywords: bed load, grain size distribution, sedimentation, lesti river, sengguruh dam